Nutrient Intake and Digestibility of Beef Cattle Fed with Ration Containing Soybean Pod - Arief Saepudin; Lilis Khotijah; Sri Suharti (Buletin Ilmu Makanan Ternak, 2016)
Soybean pod are potential as feed sources for beef cattle. They contain 5.5% crude protein, 35.4% crude fiber, acid detergent fiber 51.4%, and 12.9% lignin. The aims of this study was to analyze the optimal level of soybean pod utilization as Madura cattle ration and to asses its effect on intake and digestibility of nutrients. The study used 12 heads Madura cattle and kept in the individual cage for 90 days. The study used randomized complete block design with 4 treatments and 3 replications. The treatments were T0: grass only (negative control), T1: grass + concentrate with ratio 40:60 (positive control), T2: complete ration of 15% soybean pod, T3: complete ration of 30% soybean pod. Parameter observed were nutrient intake and digestibility. The results showed that the use of soybean pod up to 30% in ration significantly increased (P<0.05) nutrients intake and digestibility compared to the control ration (grass only) and similar with the used of grass + concentrate ration (positive control). In conclusion, soybean pod have potency as feed sources and the use of soybean up to 30% in the complete ration have positive effect on intake and digestibility of nutrients.